2019
DOI: 10.3390/cryst9050252
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Internal Free Surfaces on Void Swelling of Irradiated Pure Iron Containing Subsurface Trenches

Abstract: We studied the effects of internal free surfaces on the evolution of ion-induced void swelling in pure iron. The study was initially driven by the motivation to introduce a planar free-surface defect sink at depths that would remove the injected interstitial effect from ion irradiation, possibly enhancing swelling. Using the focused ion beam technique, deep trenches were created on a cross section of pure iron at various depths, so as to create bridges of thickness ranging from 0.88 μm to 1.70 μm. Samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…4, voids in the ion irradiated specimens appear as missing electron density in the images. It has been previously reported that injected interstitials almost always suppress void formation in both pure metals and alloys in injected region [43][44][45] . As for the near-surface region, a high density of voids exists immediately beneath the surface with no denuded zone.…”
Section: Three-dimensional Imaging Of the Defectsmentioning
confidence: 89%
“…4, voids in the ion irradiated specimens appear as missing electron density in the images. It has been previously reported that injected interstitials almost always suppress void formation in both pure metals and alloys in injected region [43][44][45] . As for the near-surface region, a high density of voids exists immediately beneath the surface with no denuded zone.…”
Section: Three-dimensional Imaging Of the Defectsmentioning
confidence: 89%
“…In Figure 4, voids in the ion irradiated specimens appear as missing electron density in the images. It has been previously reported that injected interstitials almost always suppress void formation in both pure metals and alloys in injected region [44][45][46] . As for the near-surface region, a high density of voids exists immediately beneath the surface with no denuded zone.…”
Section: Three-dimensional Imaging Of the Defectsmentioning
confidence: 89%